Glycerol Steam Reforming to Biohydrogen over Zeolite Catalyst from Geothermal Solid Waste. Issue 1 (February 2021) - Widayat,; Philia, J; Dwilaksana, M I; Luthfi, A
Abstract: Glycerol (C3 H8 O3 ) is a polyhydric alcohol compound with three hydroxyl groups in one molecule, polar and viscous in nature. Glycerol can be obtained through the transesterification process in the biodiesel industry, the saponification process in the soap industry and the hydrolysis process in the fatty acid industry. The research method follows two partss, which is catalyst synthesis and steam reforming process. The zeolite catalyst was characterized using X-Ray Diffraction (XRD) to determine crystal characteristic, Scanning Electron Microscopy (SEM) to identify the morphology of the catalyst, and surface area by using BET method. Zeolite catalyst have analcime diffraction pattern Performance of zeolite catalyst was evaluated trough glycerol steam reforming process. The biohydrogen yield increased up to 47% by using zeolite catalyst. Reaction temperature is a parameter that affected to the biohydrogen yield .